Analisis Pengaruh Pendapatan, Pengalaman Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan pada CV. Aujel Perkasa Abadi di Kecamatan Batin XXIV dalam Perspektif Islam - Sumantri Sumantri; Niki Kosasih; Akhmadi Akhmadi (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of income, work experience, and the work environment on employee performance at CV. Aujel Perkasa Abadi in Batin XXIV District. Data collection was conducted by administering questionnaires to respondents. The study sample consisted of 60 respondents. The results indicate that, simultaneously, income, work experience, and the work environment have a significant influence on employee performance; however, when analyzed individually (partially), only income was found not to have a significant effect on employee performance at CV. Aujel Perkasa Abadi in Batin XXIV District.